Optimising orthodox style learning in physical education through a variational training model - Endrawan, I Bagus; Martinus; Septaliza, Dewi; Muslimin; Alam, M. Hafizin (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background: The research problem is to improve our understanding of how different training approaches can improve bullet-shot results. Research Objectives: This study aims to investigate the impact of different training models on the learning outcomes of orthodox-style shot put. Methods: The research method employed was an experiment with a one-group pre-test and post-test design to enhance student learning outcomes using a varied training model. The subjects consisted of 32 students from a high school in Palembang. The study was conducted over 30 days, with four weekly meetings. During each meeting, 2-3 training models were presented, resulting in a total of 10 variation training models, namely Passing Techniques in Football Baseball, Techniques that Hold the Repulsion, Hanging the Ball, Resisting Pull, Clap Hand, Reject Target, Throwing Darts, Shoot in Target, and Load Rejection One Shoot. Data analysis used SPSS version 23 to calculate the significant value of the pretest and posttest results. Finding/Results: The study found that using varied training models resulted in significantly better learning outcomes in orthodox-style bullet throwing. Conclusion: The study concluded that varied training models have a considerable positive influence on learning outcomes in the orthodox style of instruction. This suggests that the findings contribute to a deeper understanding of effective training methods in sports education and have practical implications for athletic training programs. We could conduct longitudinal studies to investigate the long-term impact of diverse training on skill retention and entry into competitive athletics.